Prevalence of Mycobacterium tuberculosis Beijing genotype and its association with drug resistance in North India - Jitendra P. Mathuria; Govind N. Srivastava; Pragya Sharma; Bharat L. Mathuria; Sanjay Ojha; Vishwa M. Katoch; Shampa Anupurba (Elsevier, 2017)
The global presence and rapid dissemination of Beijing genotype of Mycobacterium tuberculosis, makes it an important issue of public health. Its presence and association with multi-drug resistance has been shown in many settings. In present study we tried to find its prevalence and association with drug resistance in North India. One hundred and twenty four M. tuberculosis isolates were analyzed with spoligotyping, further drug susceptibility testing was done by 1% proportional method. Out of these, 11 (8.9%) M. tuberculosis isolates were identified as Beijing and 113 (91.1%) as non-Beijing genotypes. While looking at their drug susceptibility patterns, 6 (54.5%) & 22 (19.5%) were found to be multi drug resistant (MDR) among Beijing and non-Beijing isolates respectively. Our study concluded that the Beijing strains were not so common in north India and these strains do not fully associate with MDR. Keywords: Mycobacterium tuberculosis, Spoligotyping, Beijing, MDR, Drug resistance